2019
DOI: 10.1002/oby.22539
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Overvaluation of Shape or Weight in Binge‐Eating Disorder: Results from a National Sample of U.S. Adults

Abstract: Objective: This study aimed to examine the prevalence of overvaluation of shape or weight in a nationally representative sample of U.S. adults with binge-eating disorder (BED) and to compare functioning correlates using a group of adults with bulimia nervosa (BN). Methods: Participants included 207 respondents from the National Epidemiologic Survey on Alcohol and Related Conditions who met Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition) diagnoses of BED (n = 163) or BN (n = 44). Sociodemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
(47 reference statements)
2
17
0
Order By: Relevance
“…Next, although our clinic documents DSM-5 eating disorder diagnoses as routine practice, we did not capture diagnoses by validated semi-structured interviews. Furthermore, we included a spectrum of other-ED, including diagnoses in which overvaluation of body shape/weight is not diagnostic (by DSM-5); for example, not all patients with BED in the community have significant overvaluation of shape/weight (Forrest, Jacobucci, & Grilo, 2020) and in fact some research findings support shape/weight overvaluation presence as a diagnostic specifier for BED (Coffino, Udo, & Grilo, 2019). Finally, although we checked to ensure no MTurk workers completed our study twice and invited individuals to participate via an email from MTurk only if they had qualified based on the screener, we did not implement other checks to ensure quality of MTurk participants.…”
Section: Discussionmentioning
confidence: 99%
“…Next, although our clinic documents DSM-5 eating disorder diagnoses as routine practice, we did not capture diagnoses by validated semi-structured interviews. Furthermore, we included a spectrum of other-ED, including diagnoses in which overvaluation of body shape/weight is not diagnostic (by DSM-5); for example, not all patients with BED in the community have significant overvaluation of shape/weight (Forrest, Jacobucci, & Grilo, 2020) and in fact some research findings support shape/weight overvaluation presence as a diagnostic specifier for BED (Coffino, Udo, & Grilo, 2019). Finally, although we checked to ensure no MTurk workers completed our study twice and invited individuals to participate via an email from MTurk only if they had qualified based on the screener, we did not implement other checks to ensure quality of MTurk participants.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that anorexia nervosa psychopathology is similar in adults and adolescents, and contrasts with recent data provided by Christian et al (), who they found significant differences in eating disorder psychopathology networks across developmental stages. However, their data pertain to a transdiagnostic sample, including patients with a diagnosis of binge‐eating disorder, in which, as mentioned, overvaluation of shape and weight is only present in half of cases (Coffino, Udo, & Grilo, ). Furthermore, the majority of their participants did not have a clinician‐informed diagnosis of an eating disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbance in the experiencing of weight and shape is a central cognitive facet of bulimia nervosa (BN; APA, 2013), anorexia nervosa (AN), and binge‐eating disorder (BED) (Coffino, Udo, & Grilo, 2019; Wilfley, Schwartz, Spurrell, & Fairburn, 2000). Within the Diagnostic and Statistical Manual of Mental Disorders (DSM), criteria related to body image disturbance were first introduced for BN and AN in the DSM‐III (APA, 1980) as “overconcern about shape and weight,” which was later changed to “undue influence of body weight or shape on self‐evaluation” in the DSM‐IV (APA, 1994) and maintained in the DSM‐5 (2013).…”
Section: Introductionmentioning
confidence: 99%